Mechanical characterisation of float and laminated glass - Adeniran, Adebowale Ebenezer (Department of Mechanical Engineering, 2025)
In recent years, glass has experienced growth in its application within engineering and architecture, especially for structural applications [1]. It has been used as various components such as balcony walls, staircases, floors, roofs, and fa¸cades. As demand for secure and safe construction continues to grow, there is an increasing interest in the mechanical characterisation of glass, particularly laminated glass (LG) and float glass (FG), which are the most commonly used types in various applications. Despite its growth, the understanding of the structural behaviour of glass and mechanical properties is still not as advanced as that of other construction materials like concrete, steel, and wood [2]. During production, glass undergoes several processes, including melting of raw materials, annealing, cutting, and transportation. These processes introduce micro-flaws on the edges and surfaces of the glass. Also, the exposure of glass to mechanical stress, temperature fluctuations, impacts, or improper handling and installation further contributes to the formation of these micro-flaws [3, 4]. The quantity of these micro-flaws often depends on the geometry of the glass and plays an essential role in evaluating glass failure stress, which ultimately affects its structural integrity and safety. The fracture strength of glass materials is highly sensitive to micro-flaws, which act as stress concentrators and initiate cracks [5]. For a given flaw density, as the volume increases, the number of flaws, and, in particular, the number of flaws of critical length, increases [6]. This gives rise to the size effect, where the fracture strength of the specimen will decrease as the size of the specimen increases [7]. The study is set to determine the influence of the size of the loading span on the fracture strength of FG and LG when subjected to the four-point bend test (FPBT) and the ring-on-ring (ROR) test. This will aid in developing guidelines that account for size effects in structural design, ensuring safer and more reliable use of glass materials in engineering and architectural applications. The FPBT setup strictly adhered to ASTM C158-02 guidelines, while the ROR test followed ASTM C1499-19 standards. The tests reveal that both FG and LG demonstrate elastic behaviour with no plastic deformation, and mainly fail through brittle fracture. In both the FPBT and ROR tests, it is observed that the fracture strength of FG and LG is higher with smaller loading spans compared to larger loading spans. Additionally, the ROR results show more variability than the FPBT results. The study reveals that the Weibull distribution is suitable for describing the fracture strength of glass materials under stress. Moreover, the experimental fracture strengths were calculated analytically and confirmed using finite element analysis (FEA). The study provides important information about the performance and reliability of both FG and LG in real-world applications, especially in construction and automotive industries where durability and safety are paramount.